EFICIENCIA MASTICATORIA ENTRE PORTADORES DE PRÓTESIS TOTALES Y SOBREDENTADURAS INFERIORES (2014)
Objective: to assess the masticatory performance among complete dental and implant overdenture wearers.Methods: a quasi-experimental study was done. The masticatory efficiency was evaluated in fifteen complete dentures wearers and fifteen upper dentures and lower overdenture wearers. The subjects filled out a satisfaction questionnaire and chewed a piece of 6 g of raw carrots. The particles were issued in the oral cavity and evaluated towers sieves of different diameters superimposed in descending order. Thus the percentage value for each sieve was obtained. The Chi2 or Fisher exact test for qualitative variables and Student t test or Mann-Whitney U for quantitative variables according to their distribution were carriet out. A value of p<0.05 was considered statistically significant.Results: a statistically significant difference between groups regarding satisfaction, need to remove the prosthesis and chewing comfort was not found. A better masticatory performance was seen in 85% and 14% of the implant overdentures and complete dental wearers, respectively. This difference was statistically significant (p<0.0001).Conclusions: masticatory performance in patients with prosthetic overdenture on two axial type implants was different when compared with patients with complete dentures.